2017
DOI: 10.1155/2017/3480413
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Modality Is Differentially Associated with Neurocognition in Older Adults

Abstract: This study explored the effects of exercise modality and type of fitness index on cognitive function in the older adults as assessed via behavioral and neuroelectrical approaches. Sixty older adults were assigned to an aerobic exercise, a coordination exercise, or a control group based on their previous exercise experience. The participants completed congruent and incongruent trials of a modified Stroop Test, during which, event-related potentials were recorded. The participants also completed multiple physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
2
19
0
2
Order By: Relevance
“…Across studies, evidence supported a relationship of physical activity on P3b from early to late adulthood, with increased physical activity related with larger P3b amplitude (Chang, Chu, et al, ; Chang, Huang, et al, ; Dai et al, ; Fong et al, ; Hillman et al, , ; Polich & Lardon, ; Tsai & Wang, ; Wang & Tsai, ; see example in Figure b), shorter P3b latency (Chang, Huang, et al, ; Fong et al, ; Hillman et al, , ; Kamijo & Takeda, ), or greater neural efficiency as reflected by a larger capacity for upregulating P3b amplitude when task demand increased (Gajewski & Falkenstein, ; Kamijo & Takeda, ). These associations may be moderated by age—as topographic shifts in the expression of P3b on the scalp differ with age (McDowell et al, ) as well as for open‐skill compared to closed‐skill activities, which were associated with larger increases in P3b amplitude (Chang, Chu, et al, ; Tsai & Wang, ; Tsai, Wang, et al, ) and more localized scalp distribution of P3b amplitude (Huang, Lin, Hung, Chang, & Hung, ). Although null associations of physical activity with P3b were found in three studies, these findings may be related to methodological decisions such as unspecified windows for measuring P3b (Hawkes et al, ) or tasks designed to elicit different subcomponents of P3 complex (Getzmann et al, ) or to only assess simple RT (Berchicci et al, ).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Across studies, evidence supported a relationship of physical activity on P3b from early to late adulthood, with increased physical activity related with larger P3b amplitude (Chang, Chu, et al, ; Chang, Huang, et al, ; Dai et al, ; Fong et al, ; Hillman et al, , ; Polich & Lardon, ; Tsai & Wang, ; Wang & Tsai, ; see example in Figure b), shorter P3b latency (Chang, Huang, et al, ; Fong et al, ; Hillman et al, , ; Kamijo & Takeda, ), or greater neural efficiency as reflected by a larger capacity for upregulating P3b amplitude when task demand increased (Gajewski & Falkenstein, ; Kamijo & Takeda, ). These associations may be moderated by age—as topographic shifts in the expression of P3b on the scalp differ with age (McDowell et al, ) as well as for open‐skill compared to closed‐skill activities, which were associated with larger increases in P3b amplitude (Chang, Chu, et al, ; Tsai & Wang, ; Tsai, Wang, et al, ) and more localized scalp distribution of P3b amplitude (Huang, Lin, Hung, Chang, & Hung, ). Although null associations of physical activity with P3b were found in three studies, these findings may be related to methodological decisions such as unspecified windows for measuring P3b (Hawkes et al, ) or tasks designed to elicit different subcomponents of P3 complex (Getzmann et al, ) or to only assess simple RT (Berchicci et al, ).…”
Section: Resultsmentioning
confidence: 91%
“…The findings in 16 of the 19 (84.2%) reviewed studies showed associations of physical activity with the P3b‐ERP during performance on cognitive control and attention tasks (Chang, Chu, et al, ; Chang, Huang, Chen, & Hung, ; Dai, Chang, Huang, & Hung, ; Fong, Chi, Li, & Chang, ; Gajewski & Falkenstein, ; Hatta et al, ; Hillman, Kramer, Belopolsky, & Smith, ; Huang, Lin, Hung, Chang, & Hung, ; Kamijo & Takeda, , ; Tsai & Wang, ; Tsai, Wang, et al, ; Wang & Tsai, ), despite no effects in behavioral outcomes in three of the 19 (15.8%) studies (Hillman, Belopolsky, Snook, Kramer, & McAuley, ; McDowell, Kerick, Santa Maria, & Hatfield, ; Polich & Lardon, ). Two studies (10.5%) found improved task performance for active compared to inactive older adults, while no differences in P3b were observed between groups (Getzmann, Falkenstein, & Gajewski, ; Hawkes, Manselle, & Woollacott, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies on the cognitive benefits of mind-body exercises have not generally focused on neurological mechanisms, but those which did have primarily utilized electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) (Chang et al, 2017;Tao et al, 2017b). Functional nearinfrared spectroscopy (fNIRS) is a neuroimaging technique for investigating cortical hemodynamic responses (Chen T.T.…”
Section: Introductionmentioning
confidence: 99%